Journey to the East : the Jesuit mission to China, 1579-1724 - Brockey, Liam Matthew (Cambridge, Mass. : Belknap Press of Harvard University Press, 2007)
It was one of the great encounters of world history: highly educated European priests confronting Chinese culture for the first time in the modern era. This & ldquo;journey to the East & rdquo; is explored by Liam Brockey as he retraces the path of the Jesuit missionaries who sailed from Portugal to China, believing that, with little more than firm conviction and divine assistance, they could convert the Chinese to Christianity. Moving beyond the image of Jesuits as cultural emissaries, his book shows how these priests, in the first concerted European effort to engage with Chinese language and thought, translated Roman Catholicism into the Chinese cultural frame and eventually claimed two hundred thousand converts. The first narrative history of the Jesuits & mission from 1579 until the proscription of Christianity in China in 1724, this study is also the first to use extensive documentation of the enterprise found in Lisbon and Rome. The peril of travel in the premodern world, the danger of entering a foreign land alone and unarmed, and the challenge of understanding a radically different culture result in episodes of high drama set against such backdrops as the imperial court of Peking, the villages of Shanxi Province, and the bustling cities of the Yangzi Delta region. Further scenes show how the Jesuits claimed conversions and molded their Christian communities into outposts of Baroque Catholicism in the vastness of China. In the retelling, this story reaches across continents and centuries to reveal the deep political, cultural, scientific, linguistic, and religious complexities of a true early engagement between East and West.
Preface -- Note on translations and orthography -- Introduction -- PART I. CHARTING THE COURSE. An uneasy foothold -- In the shadow of greatness -- Witnesses to armageddon -- The problem of success -- Between tolerance and the intolerable -- PART II. BUILDING THE CHURCH. In the apostles' classroom -- Learning the language of birds -- The business of conversion -- A good method and order -- Brothers of passion and mercy -- Conclusion -- Bibliographic note -- Notes -- Illustration credits -- Index.
Includes bibliographical references (pages 427-477) and index.
Print version record.
In English.
Master record variable field(s) change: 650
Keywords: Jesuits -- Missions -- China; Jesuits; China -- Church history; RELIGION -- Christian Ministry -- Missions; Missions; China; History; Modern History .; Theologie, Christentum; Electronic books; Church history